Professionalism and Technical Assistance Skills of Master Teachers in Relation to Teachers’ Performance (International Journal of Scientific Research and Management (IJSRM), 2023)
The main concern of this study is to determine the professionalism and technical assistance skills of master teachers in relation to teachers’ performance. Specifically, the study aimed to find out the profile of the respondents in terms of the following selected variables: age, highest educational attainment, and length of service. The instrument used in this study was a self–made questionnaire. The level of professionalism of Master Teachers’ in terms of the following areas; Attitudes towards peers and superiors, Attitudes towards stakeholders and attitudes towards learners and the Technical Assistance Skills of Master Teachers’ in terms of the following areas; Capability building, Information Sharing, and Group Work Management were assessed. It was conducted in the Division of Bacolod City and the respondents of the study were the 164 master teachers and 45 school heads in the elementary level. The instrument to gather the data of the study was a self-made questionnaire. Findings revealed that there are 45 school heads in the study whom the majority are older. In terms of highest educational attainment, the majority are from lower (MA Graduate). In terms of length of service, the majority are from longer in service (8 years and more). There are 164 master teachers in the study whom the majority are older. In terms of highest educational attainment majority are from higher (MA & Ph.D. Graduate) In terms of length of service, the majority are from longer in service (5 years and more). The level of professionalism and the level of technical assistance of master teachers in terms of the areas as assessed by the school heads and the master teachers is Very High. The level of professionalism of master teachers in terms of the areas as assessed by the school heads when they are grouped according to age, highest educational attainment, and length of service is Very High. The level of professionalism of master teachers in terms of the areas as assessed by the master teachers themselves is High for younger, lower and shorter in service and is Very High for older, higher and longer in service. The level of technical assistance of master teachers in terms of the areas as assessed by the school heads when they are grouped according to age, highest educational attainment, and length of service is Very High. The level of technical assistance of master teachers in terms of the areas as assessed by the master teachers themselves when they are grouped according to age is Very High. According to highest educational attainment, for lower is High and for higher is Very High. For the length of service, shorter was high, and longer in service is Very High. The level of teachers’ performance during the School Year 2019 – 2020 is Very Satisfactory. No significant differences existed in the levels of professionalism of master teachers as assessed by the school heads and the master teachers themselves in the area of attitudes towards peers and superiors and attitudes towards learners. But significant difference is shown in the area of attitudes towards stakeholders. No significant differences existed in levels of technical assistance skills of master teachers as assessed by the school heads and the master teachers themselves in the area of capability building, information sharing, and group work management. No significant relationship existed between the level of professionalism of master teachers as assessed by the school heads and master teachers themselves and the teachers’ performance. No significant relationship exists between the level of technical assistance skills of master teachers as assessed by the school.